Transgenic crops, production risk, and agrobiodiversity - Krishna Vijesh; Matin Qaim; David Zilberman (University of Bonn, Center for Development Research (ZEF), 2014)
Do transgenic crops cause agrobiodiversity erosion? We hypothesize that they increase productivity and reduce production risk and may therefore reduce farmer demand for on-farm varietal diversity, especially when only a few transgenic varieties are available. We also hypothesize that varietal diversity can be preserved when more transgenic varieties are supplied. These hypotheses are tested and confirmed with panel data for the case of transgenic cotton in India. Cotton varietal diversity in India, with of over 90% adoption of transgenic technology, is now at the same level than it was before the introduction of this technology. Some policy implications are discussed.
Keywords: D24; D81; O13; O44; Q12; Q16; Q57; 330; varietal diversity; biotechnology; smallholder farmers; production risk; India